Functional Requirement of Plant Farnesyltransferase during Development in Arabidopsis - Yalovsky, Shaul (American Society of Plant Physiologists, 2000)
Arabidopsis era1 was identified as an abscisic acid–hypersensitive mutant caused by disruptions or deletions of the gene for the β subunit (AtFTB) of farnesyltransferase (FTase). The heterodimeric enzyme catalyzes the covalent attachment of the 15-carbon farnesyl diphosphate to the C terminus of regulatory proteins and is essential for growth in yeast. The first disruption of FTB in a multicellular context revealed several developmental and growth regulatory processes that require the function of FTase. The lack of FTase activity in the Arabidopsis era1-2 FTB deletion mutant resulted in enlarged meristems and organs, supernumerary organs in floral whorls, arrested development of axillary meristems, late flowering, and homeotic transformations of flowers. Complementation of era1-2 with LeFTB, the tomato gene for the β subunit of FTase, restored a normal phenotype and confirmed that the lesion is in AtFTB alone. The effect of this lesion on control of meristem size and on developmental processes suggests the involvement of regulatory proteins that require farnesylation for their function. At least three distinct processes that require the function of FTase were identified: regulation of cellular differentiation in the meristems, meristem maintenance, and regulation of flower development. Together, these results provide a basis for future studies on the involvement of FTase in specific developmental processes and for structure–function analysis of FTase in vivo.